Ethics in health services and policy : a global approach - Harris, Dean M., 1951- (San Francisco : Jossey-Bass, 2011)
"With this book nursing and health administration students can increase their understanding of the myriad global ethical issues. The book examines key issues of health services delivery (insurance, rationing of care, allocation of resources, and cost-containment) and the health care industry (corruption, kickbacks, and conflicts of interest) in both developing and developed countries. The book also considers cross-border issues that arise from the movement of patients and providers across national boundaries, such as treatment of undocumented aliens, medical tourism, and the "brain drain" of health care personnel from developing countries"--Provided by publisher.
Machine generated contents note: Introduction. -- Acknowledgments. -- The Author. -- 1 Ethical Theories and Bioethics in a Global Perspective. -- Theories of Ethics. -- Are Theories of Ethics Global? -- Can Theories of Ethics Encourage People to Do the Right Thing? -- 2 Autonomy and Informed Consent in Global Perspective. -- Ethical Principles and Practical Issues of Informed Consent. -- Does Informed Consent Really Matter to Patients? -- Is Informed Consent a Universal Principle or a Cultural Value? -- 3 Withholding or Withdrawing Treatment and Physician-Assisted Suicide. -- Withholding or Withdrawing Treatment at the End of Life. -- Assisting Patients in Committing Suicide. -- 4 Ethical Issues in Reproductive Health. -- Ethics of Abortion in Different Times, Places, and Cultures. -- Current Ethical Issues in Abortion. -- Assisted Reproductive Technology and Stem Cell Research. -- Emergency Contraception. -- Ethics of Imposing Conditions on Funding. -- 5 Ethical Issues of Female Genital Mutilation. -- The Facts About FGM. -- FGM as a Challenge to Ethical Relativism. -- Ethics of FGM for Adult Women. -- 6 Ethical Issues of Research with Human Subjects. -- Background Information and the Belmont Report. -- Autonomy and Voluntary Informed Consent. -- Beneficence and Cost-Benefit Analysis. -- Issues of Justice and Fairness for Human Subjects. -- 7 The Right to Health Care, and Ethical Obligations to Provide Care. -- Is There an Ethical Right to Health Care? -- Ethical Obligations of Health Care Professionals. -- Ethical Obligations of for-Profit Health Care Providers. -- 8 Ethical Issues in Rationing and Allocation of Limited Resources. -- Levels of Allocating Resources. -- Methods of Rationing Health Resources. -- Comparative Effectiveness Research and Cost-Effectiveness Analysis. -- 9 Ethical Issues of Health Insurance and Health System Reform. -- Ethical Issues in Financing Health Services and Designing Insurance Systems. -- Fundamental Values of Health Systems. -- 10 Ethical Issues in the Movement of Patients Across National Borders. -- Ethical Duties to Provide Health Care to Undocumented Aliens. -- Ethical Issues in Medical Tourism. -- 11 Ethical Issues in the Movement of Health Care Professionals Across National Borders. -- Ethical Issues in the Migration of Health Professionals. -- Proposed Solutions and Their Ethical Implications. -- Fair Treatment of Health Care Workers from Other Countries. -- 12 Corruption and Informal Payments in Health Systems. -- Payment of Informal Fees by Patients and Their Families. -- Is Corruption Bad for Your (and Other People's) Health? -- References. -- Index.
Includes bibliographical references and index.
Keywords: Medical ethics; Medical care; Ethics, Medical; Delivery of Health Care -- ethics